Failure modes and interaction mechanisms of tunnel under active landslide conditions - Wenjiao Zhou; Jiawei Fan; Shumao Qiu; Yufang Zhang (Scientific Reports)
Abstract The construction of tunnels can easily trigger the reactivation of old landslide bodies, posing a threat to the transportation safety. In this study, using methods such as engineering geological investigation, slope deformation monitoring, deep displacement monitoring, and numerical simulation, the interaction between landslides and tunnels was investigated from the perspective of landslide deformation and failure characteristics. The Walibie Tunnel (WLBT) of Shangri-La to Lijiang (XL) expressway was taken as an example. The results showed that there were two unstable slopes developed in the upper part of the tunnel, with the new active landslides. Shallow and deep creeping deformation zones also exist within the landslide area. Combining the position of the deformation zones of the unstable slopes and the actual tunnel damage observed, it was determined that the failure mode of the tunnel was longitudinal tensile fracture in the traction section-tunnel. Numerical simulation and field investigation revealed the mechanism of interaction between the WLBT and landslides: the traction section of the tunnel passed through the unstable slope parallelly, and during the continuous opening and expansion process at the rear edge of the unstable slope, a significant tensile force was exerted on the tunnel, resulting in initial tensile fracture damage.